Teste de permeabilidade intestinal de acúcares como marcadores não invasivos de intolerância a lactose - Correia, Ricardo Aires (2007)
The intolerance to carbohydrates, especially to lactose, is due to a number of factors, particularly the deficiency of lactase. The development of such intolerance is influenced by genetic and environmental issues. The diagnosis of the adult type hipolactasemia is usually based on the lactose intolerance invasive test, which varies in sensibility from 74% to 94%, and in specificity from 77% to 96%. Objective. The study used a non-invasive test to establish simultaneously the integrity of the mucosa (presence or absence of injury), the extension of compromised area, the mucosal permeability and the enzymatic integrity (disaccharidases) of the enterocyte brush border. Material and Method. The HPLC (High Performance Liquid Chromatography) technique was applied towards determining the urinary excretion of lactose, lactulose, mannitol and sucrose. It was a case-control study, in which cases were pacients with flat-curved lactose tolerance test, meanwhile controls were individuals with normal-curved lactose tolerance test. 65 adults varying from 21 to 68 years old were selected, being the lactose tolerance test negative for 31 and positive for 34 of them. Results. The excretion curves of lactulose (p=0.103) and mannitol (p=0.3511) were not, by themselves, a defining parameter to diagnose lactose intolerance. However, the lactulose/mannitol excretion rate (p=0.0741), in spite of being a marginal value, revealed that such parameter indicates disturbance of mucosal permeabilily induced by lactose intolerance. The analysis of the ROC (Receiver Operating Characteristic) curve expressed, over the relation lactulose/mannitol excretion rate, a 61.76% sensibility and a 60.00% specificity, in a cutting edge of 0.0015. The lactose excretion curve evaluated p=0.1317 did not reveal to be a significant parameter to diagnose lactose intolerance. The research comprised the stratification of the correlation lactulose/mannitol excretion rate and lactulose excretion with or without usual ethylic ingestion. When no usual ethylic ingestion was observed, the lactulose/mannitol excretion rate did not showed as a positive predictive value for lactose intolerance at p=0.0876. On the other hand, no predictive value (p=0.2676) was found when usual ethylic ingestion was verified. Conclusions. The outcome suggests that the test in vivo to determine the urinary excretion of lactose, lactulose, mannitol and sucrose proved itself appropriated as a parameter for the functional evaluation of intestinal mucosa. Althout is not enougth specific and sensible to be used as parameter to diagnosis lactose intolerance. The usual ethylic ingestion d’ont induces disturbance of functional intestinal barrier and might not interfere in the result of the sugar excretion difference test.